2012
DOI: 10.12659/msm.883538
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of human cerebrospinal fluid as a diagnostic biomarker in patients with meningioma

Abstract: SummaryBackgroundTo identify meningioma-specific proteins, cerebrospinal fluid (CSF) from 4 patients with a meningioma and 4 patients with a non-brain tumorous lesion were analyzed.Material/MethodsTwo-dimensional electrophoresis and electrospray quadrupole time-of-flight tandem mass spectrometry analyses revealed 10 unique spots, containing 11 independent proteins (spot #2 and #4 each contained 2 proteins and spot #3 was not identified) were evident in CSF associated with human meningioma: serum albumin precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Comparative tissue proteomic profiling of MGs can provide mechanistic insights of the pathogenesis and molecular basis of the tumorigenesis. There are a few earlier reports, where proteomic studies have been conducted on MG cell lines, tissue, and CSF samples, describing differential expression of proteins in different grades of MGs . In the current study, comparative tissue proteomic analysis of control samples and different grades of MGs was performed by iTRAQ‐based quantitative proteomics by using ESI‐Q‐TOF and Q‐Exactive MS. As far our knowledge goes, this is the first iTRAQ‐based comprehensive quantitative proteomics analysis of tissue samples from different grades of human MGs.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative tissue proteomic profiling of MGs can provide mechanistic insights of the pathogenesis and molecular basis of the tumorigenesis. There are a few earlier reports, where proteomic studies have been conducted on MG cell lines, tissue, and CSF samples, describing differential expression of proteins in different grades of MGs . In the current study, comparative tissue proteomic analysis of control samples and different grades of MGs was performed by iTRAQ‐based quantitative proteomics by using ESI‐Q‐TOF and Q‐Exactive MS. As far our knowledge goes, this is the first iTRAQ‐based comprehensive quantitative proteomics analysis of tissue samples from different grades of human MGs.…”
Section: Discussionmentioning
confidence: 99%
“…The peak 1969.9 Da, which is a fragment of transthyretin precursor, was more highly expressed in lung adenocarcinoma patients than in healthy controls in our study. Previous data illustrated that peaks of transthyretin precursor (TTR) fragments have frequently been detected in papillary thyroid cancer, pancreatic carcinoma and meningioma after a MALLDI-TOF method (10,15,17). One of the peaks associated with TTR was reported to be overexpressed in papillary thyroid cancer and has been identified as fragment of TTR by 2-DE, MALDI-TOF/MS and Western blot (10).…”
Section: Discussionmentioning
confidence: 99%
“…A fragment of TTR was reported as being overexpressed in serum of pancreatic carcinoma patients receiving low dose of warfarin but not in those on high dose of warfarin using iTRAQcoupled LC-MS/MS (17). Other studies have identified an specific cleavage fragment of TTR in human cerebrospinal fluid of patients with meningioma using two-dimensional electrophoresis and electrospray quadrupole timeof-flight tandem mass spectrometry analysis (15).All these suggested the potential of 1969.9 Da as a biomarker for cancer and the possible relationship between TTR and lung adenocarcinoma, which would be explored in our further work. In addition, peak m/z 2213.4 Da, another peptide in our model for lung adenocarcinoma patients, is one fragment of fibrinogen alpha chain precursor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that specific proteomic patterns can differentiate subtypes or grades of human brain tumors. [27][28][29][30] Modern technological advancements in protein quantification which Highly specific [12][13][14]16] Low sensitivity and false negative results are common [3,13,20,23,24] Flow cytometry analysis:…”
Section: Proteomic Analysis Of Csfmentioning
confidence: 99%
“…These techniques have the ability to detect genetic aberrations as a sign of malignancy location [26] Low sensitivity [26] Detection of biochemical molecules secreted by cancers to the CSF CSF proteomic analysis: Systematic identification and quantification of the complete complement of proteins in the CSF Specific proteomic patterns can differentiate subtypes or grades of specific brain tumors [27][28][29][30] Limited sensitivity and specificity [31] CSF microRNAs analysis: Measuring microRNA Profiling of CSF High specificity and chemical stability [60,101] Only small amounts of CSF samples are required for the detection of miRNAs in the CSF offers the advantage of convenient repetitive monitoring of molecular events happening in cancer in the response to treatment [76] The unknown origin and factors influence their level of expression might impact their specificity as biomarkers [76,[102][103][104][105][106] CSF: cerebrospinal fluid provide rapid screening, low sample consumption, and accurate protein identification, have enhanced the precision of proteomic analyses and are anticipated to accelerate brain tumor biomarker discovery. [31] Research work on traditional sampling sources for proteomic profiling, such as blood [31,32] and tissue lysates, [33] have yielded asubstantial amount of information on potential brain cancer biomarkers.…”
Section: Proteomic Analysis Of Csfmentioning
confidence: 99%